Some helminths in certain mammals of Spitzer's slough - McDowell, John W., author; Krull, Wendell Henry, advisor; Fults, Jess Lafayette, 1910-, committee member; Jensen, Rue, committee member; Deem, Arthur W., committee member; List, George M. (George Milton), 1885-1956, committee member (Colorado State University. Libraries, 1948)
To view the abstract, please see the full text of the document.
Keywords: Helminths; Mammals -- Parasites